2019
DOI: 10.1101/568725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating genomic data for management of local adaptation in a changing climate: A lodgepole pine case study

Abstract: The need for tools to cost-effectively identify adaptive variation within ecologically and 13 economically important plant species is mounting as the detrimental effects of climate change 14 become increasingly apparent. For crop and wild populations alike, mismatches between adaptive 15 variation and climatic optima will reduce health, growth, survival, reproduction, and continued 16 establishment. The ease with which land managers can quantify the relative importance of different 17climate factors or the spa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 87 publications
4
20
0
Order By: Relevance
“…This finding, combined with outcomes from the Illingworth provenance trials in British Columbia (e.g., Rehfeldt et al., 1999, 2001; Ying & Liang, 1994), supports the notion that P. contorta populations are locally adapted to somewhat narrower ranges of climatic conditions than are present across its entire range. Cold‐tolerance, for example, may have affected survival in our study, a characteristic observed to strongly affect P. contorta survival and growth (Liepe et al., 2016; Mahony et al., 2020; Rehfeldt et al., 1999, 2001; Wang et al., 2010). In our experiment, murrayana and contorta populations had strikingly low survival in the cooler latifolia garden (Figure 3c), suggesting maladaptation to the extreme winter temperatures of this intermountain climate.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This finding, combined with outcomes from the Illingworth provenance trials in British Columbia (e.g., Rehfeldt et al., 1999, 2001; Ying & Liang, 1994), supports the notion that P. contorta populations are locally adapted to somewhat narrower ranges of climatic conditions than are present across its entire range. Cold‐tolerance, for example, may have affected survival in our study, a characteristic observed to strongly affect P. contorta survival and growth (Liepe et al., 2016; Mahony et al., 2020; Rehfeldt et al., 1999, 2001; Wang et al., 2010). In our experiment, murrayana and contorta populations had strikingly low survival in the cooler latifolia garden (Figure 3c), suggesting maladaptation to the extreme winter temperatures of this intermountain climate.…”
Section: Discussionmentioning
confidence: 68%
“…Local declines are likely in portions of the species’ distribution where, despite predicted increases in precipitation (Mahony et al., 2017), concurrent temperature increases will change the timing and type of precipitation (e.g., from snow‐ to rain‐dominated precipitation; Buma et al., 2019) and thus growing‐season water availability. Given that drought is expected to become increasingly common across its range (Coops & Waring, 2011; Mahony et al., 2020), drought adaptation may be key to local P. contorta population persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the combined candidate loci detected in GEA and GPA, using both univariate and multivariate methods, we improved the detection of single‐locus and multilocus adaptive signals. (Mahony et al., 2019; Talbot et al., 2016; Vangestel et al, 2018)⁠. Interestingly, more intersections between GEA and GPA were found when using RDA than when using LFMM (Figure 3), indicating that most adaptations to local environmental conditions expressing differential phenotypes are polygenic (Forester et al., 2018)⁠.…”
Section: Discussionmentioning
confidence: 99%
“…While the assessment of phenotype through common garden and reciprocal transplant experiments to identify local adaptations has a long history (Aitken & Bemmels, 2016)⁠, no study has yet combined genotype‐environment associations (GEA) with genotype‐phenotype associations (GPA) to delineate seed sourcing areas. This approach could improve the inference of potential candidate genes and provide important insights into genes underlying fitness‐related traits (Mahony et al., 2019; Talbot et al., 2016; Vangestel, Eckert, Wegrzyn, St. Clair, & Neale, 2018)⁠.…”
Section: Introductionmentioning
confidence: 99%